2020
DOI: 10.3390/jcm9082486
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Cognitive and Emotional Factors and Healthcare and Medication Use in People Experiencing Pain: A Systematic Review

Abstract: Pain conditions are among the leading causes of global disability, impacting on global healthcare utilization (HCU). Health seeking behavior might be influenced by cognitive and emotional factors (CEF), which can be tackled by specific therapies. The purpose of this study was to systematically review the evidence concerning associations between CEF and HCU in people experiencing pain. Three databases were consulted: PubMed, Web of Science and EconLit. Risk of bias was assessed using the Downs and Black Checkli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 162 publications
(773 reference statements)
0
13
0
Order By: Relevance
“…These findings align with previous prognostic studies analysing factors associated with general healthcare utilization. 7,15,16,18,[21][22][23][24] Notably, while the mean scores for neuroticism (and all other personality trait scores) for all trajectory groups were low compared to population norms, 49 they were significantly higher in the high stable trajectory group than the other trajectory groups. Higher neuroticism reflects a tendency to experience negative emotions, 70,71 and other studies have shown that neuroticism correlates with lower quality of life and reported severity of physical symptoms, 72 both of which are independently associated with high healthcare utilization.…”
Section: Multidimensional Profilingmentioning
confidence: 88%
See 2 more Smart Citations
“…These findings align with previous prognostic studies analysing factors associated with general healthcare utilization. 7,15,16,18,[21][22][23][24] Notably, while the mean scores for neuroticism (and all other personality trait scores) for all trajectory groups were low compared to population norms, 49 they were significantly higher in the high stable trajectory group than the other trajectory groups. Higher neuroticism reflects a tendency to experience negative emotions, 70,71 and other studies have shown that neuroticism correlates with lower quality of life and reported severity of physical symptoms, 72 both of which are independently associated with high healthcare utilization.…”
Section: Multidimensional Profilingmentioning
confidence: 88%
“…Several factors are associated with high levels of healthcare utilization due to pain. 7,15 These include older age, 7,15,16 low socioeconomic status, 7,16 marital status (people never married seek healthcare less often than those married) 17 and being female, 7,15,18 high pain intensity, [18][19][20] high level of disability, 18,19,21 number of pain sites, 21 comorbidity, 16 body mass index (BMI), poor general health, 15,16,22 negative health beliefs (health anxiety, catastrophizing, fear avoidance), 15,22,23 being retired or unemployed, 8 and previous healthcare use. 22,24 Personality has also been suggested as an important factor in the development of pain and coping strategies -including healthcare-seeking.…”
Section: Video Abstractmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A recent systematic review found consistent associations between pain-related anxiety/distress and treatment-seeking behaviors, including use of pain medication. 13 Baseline pain catastrophizing was a significant predictor of future pain-related office visits and total medical costs for patients with musculoskeletal pain. 14 Additionally, pain catastrophizing partially mediates the relationship between pain intensity and number of health care visits, 15 confirming that patients’ psychological and behavioral responses to their symptoms influence their healthcare utilization beyond their degree of symptomatology alone.…”
Section: Introductionmentioning
confidence: 97%
“…The cost of medical treatment and lost productivity due to pain exceeds US $635 billion each year in the United States, more than the cost of treating cardiovascular disease, cancer, or diabetes [ 5 ]. Chronic pain also significantly affects an individual’s quality of life, negatively impacting their ability to engage in day-to-day activities, and increasing risk for depression, anxiety, and opioid dependence [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%